PENGARUH EFEKTIVITAS KERJA, SEMANGAT KERJA DAN KOMPETENSI TERHADAP PRESTASI KERJA KARYAWAN PT. NUSANTARA SURYA SAKTI KLUNGKUNG - Arif Hidayatullah; Anak Agung Dwi Widyani; Ni Made Satya Utami (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
Every company organization strives to improve employee performance so that the company's goals can be achieved. Employee work performance is a result of work achieved by employees in the organization evaluating or assessing their employees. One of the factors that influence employee performance is work effectiveness, morale and competence. This study aims to analyze the effect of work effectiveness, morale, and competence on employee performance at PT. Nusantara Surya Sakti. The research method used is multiple regression analysis method. This study used 40 samples consisting of all employees of PT. Nusantara Surya Sakti. The test results on the SPSS program show that partially work effectiveness, morale, and competence have a positive and significant effect on work performance, while simultaneously work effectiveness, work morale, and competence have a significant effect on work performance. It is recommended that the company always improve the effectiveness of employees so that they can encourage employee performance and achievement to be even better, always increase employee morale and place employees according to their competencies so that they can be used as best as possible to improve individual performance.